Cannabinoid-Induced Autophagy and Heme Oxygenase-1 Determine the Fate of Adipose Tissue-Derived Mesenchymal Stem Cells under Stressful Conditions - Katharina Bublitz; Sabine Böckmann; Kirsten Peters; Burkhard Hinz (Cells, 2020)
The administration of adipose tissue-derived mesenchymal stem cells (ADMSCs) represents a promising therapeutic option after myocardial ischemia or myocardial infarction. However, their potential is reduced due to the high post-transplant cell mortality probably caused by oxidative stress and mitogen-deficient microenvironments. To identify protection strategies for ADMSCs, this study investigated the influence of the non-psychoactive phytocannabinoid cannabidiol (CBD) and the endocannabinoid analogue R(+)-methanandamide (MA) on the induction of heme oxygenase-1 (HO-1) and autophagy under serum-free conditions. At a concentration of 3 µM, CBD induced an upregulation of HO-1 mRNA and protein within 6 h, whereas for MA only a late and comparatively lower increase in the HO-1 protein could be detected after 48 h. In addition, both cannabinoids induced time- and concentration-dependent increases in LC3A/B-II protein, a marker of autophagy, and in metabolic activity. A participation of several cannabinoid-binding receptors in the effect on metabolic activity and HO-1 was excluded. Similarly, knockdown of HO-1 by siRNA or inhibition of HO-1 activity by tin protoporphyrin IX (SnPPIX) had no effect on CBD-induced autophagy and metabolic activity. On the other hand, the inhibition of autophagy by bafilomycin A1 led to a significant decrease in cannabinoid-induced metabolic activity and to an increase in apoptosis. Under these circumstances, a significant induction of HO-1 expression after 24 h could also be demonstrated for MA. Remarkably, inhibition of HO-1 by SnPPIX under conditions of autophagy deficit led to a significant reversal of apoptosis in cannabinoid-treated cells. In conclusion, the investigated cannabinoids increase metabolic viability of ADMSCs under serum-free conditions by inducing HO-1-independent autophagy but contribute to apoptosis under conditions of additional autophagy deficit via an HO-1-dependent pathway.